Evaluation of Positive Choices, a National Initiative to Disseminate Evidence-Based Alcohol and Other Drug Prevention Strategies: Web-Based Survey Study - Lexine Ann Stapinski; Smriti Nepal; Tara Guckel; Lucinda Rachel Grummitt; Cath Chapman; Samantha Jane Lynch; Siobhan Maree Lawler; Maree Teesson; Nicola Clare Newton (JMIR Publications, 2022)
BackgroundTo prevent adolescents from initiating alcohol and other drug use and reduce the associated harms, effective strategies need to be implemented. Despite their availability, effective school-based programs and evidence-informed parental guidelines are not consistently implemented. The Positive Choices alcohol and other drug prevention initiative and website was launched to address this research and practice gap. The intended end users were school staff, parents, and school students. An 8-month postlaunch evaluation of the website showed that end users generally had positive feedback on the website's usability, and following its use, most of them would consider the evidence base and effectiveness of drug education resources. This study extends this initial evaluation by examining the effectiveness and impact of the Positive Choices initiative over a 3-year period. ObjectiveGuided by the five dimensions of the RE-AIM (reach, effectiveness, adoption, implementation, and maintenance) framework, the study assessed the impact of the Positive Choices initiative in increasing awareness and implementation of evidence-based drug prevention. MethodsData were collected between 2017 and 2019, using web-based evaluation and community awareness surveys. Data from the surveys were merged to examine reach, effectiveness, adoption, implementation, and maintenance using descriptive statistics. Google Analytics was used to further understand the reach of the website. The System Usability Scale was used to measure website usability. In addition, inductive analysis was used to assess the participants' feedback about Positive Choices. ResultsA total of 5 years after launching, the Positive Choices website has reached 1.7 million users. A national Australian campaign increased awareness from 8% to 14% among school staff and from 15% to 22% among parents after the campaign. Following a brief interaction with the website, most participants, who were not already following the recommended strategies, reported an intention to shift toward evidence-based practices. The System Usability Scale score for the website was good for both user groups. The participants intended to maintain their use of the Positive Choices website in the future. Both user groups reported high level of confidence in communicating about topics related to alcohol and other drugs. Participants' suggestions for improvement informed a recent website update. ConclusionsThe Positive Choices website has the capacity to be an effective strategy for disseminating evidence-based drug prevention information and resources widely. The findings highlight the importance of investing in ongoing maintenance and promotion to enhance awareness of health websites. With the increased use and acceptability of health education websites, teams should ensure that websites are easy to navigate, are engaging, use simple language, contain evidence-informed resources, and are supported by ongoing promotional activities.